Guidance for Home Enzyme Replacement Therapy in Children and Adolescents Diagnosed with Mucopolysaccharidoses: A Scoping Review Protocol - Baeza-Fuentes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Enzyme replacement therapy is one of the main alternatives in the treatment of mucopolysaccharidosis. Conventionally, this therapy is administered in an outpatient setting, but this can be carried out at home, where the patient feels most comfortable. However, there is still a need for guidance on how to implement the use of this therapy in the home setting. This study aims to present the protocol of a scoping review that aims to identify and map the main existing guidance for the implementation of home-based enzyme replacement therapy in children and adolescents with mucopolysaccharidosis. The review protocol was developed based on the methodological guidance proposed by Peters and the PRISMA-P checklist and was registered on the Open Science Framework platform, available at OSF.IO/QUSB6. The searches will be carried out in the following databases: CINAHL, Cochrane Library, Embase, LILACS, MEDLINE, Science Direct, Scopus, and Web of Science. Gray literature will be searched in the CAPES/Brazilian Theses and Dissertations Catalog, the Brazilian Ministry of Health website, Google Scholar, the National Institute for Health and Care Excellence, and the WHO IRIS. Articles will be selected according to predefined eligibility criteria and extracted using a standardized collection form. The results of this review are expected to provide valuable insights for researchers regarding the main guidance for the implementation of home-based ERT in children and adolescents with mucopolysaccharidosis. © 2025 by the authors.